Pengaruh Intensi Terhadap Keputusan Petani Menanam Bawang Merah di Kabupaten Pesisir Selatan - Okti Diana Bahrun; Andriyono Kilat Adhi; Burhanuddin Burhanuddin (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2022)
The aims of this study were: (1) to analyze the decision of farmers in Pesisir Selatan Regency to plant shallots, (2) to analyze the intention of farmers in Pesisir Selatan Regency to plant shallots, (3) to analyze the factors that influence the decision of farmers in Pesisir Selatan Regency to plant shallots. The research adopts the theory of planned behavior and the ERG motivation theory. The research was conducted in Pesisir Selatan Regency, West Sumatra Province. This study uses primary data, which was collected through structured interviews. The research respondents were 60 farmers in Pesisir Selatan Regency. The analysis used the descriptive method and partial least square (PLS) method. The results of the analysis showed that most of the farmers in Pesisir Selatan Regency decided not to plant shallots in the next season. The intention of farmers in Pesisir Selatan Regency to plant shallots is in the high category. The decision of farmers in Pesisir Selatan Regency to plant shallots is directly and significantly positively influenced by the intention of farmers to plant shallots; and the intention of farmers to plant shallots directly and significantly positively influenced by the social norms held by farmers. Social norms are the only factor that has an indirect and significant positive effect on the decision of farmers in Pesisir Selatan Regency to plant shallots.